Differences of The Number of Maternal References In Semarang Public Health Center Based on MEOWS Scoring System - Patriajati, Aji (Diponegoro International Medical Journal, 2021)
Background: The maternal mortality rate in Semarang is 121.5 per 100,000 live births, the second-highest in Central Java. The early warning system with the Early Warning Score and the maternal emergency early warning system (PDKM) still has various shortcomings to reduce MMR.Objective: This study aims to prove the effectiveness of the application of the PDKM Modified Early Obstetric Warning System (MEOWS) as an assessment of the risk of pregnancy in primary health facilities to reduce MMR in Semarang.Methods: The study was conducted on all pregnant women who came to Tlogosari Wetan, Tlogosari Kulon, Bandarharjo, and Bangetayu public health center in Semarang and were willing to participate in the study and were referred to government hospitals using national health assurance BPJS. Sampling was done by cluster random sampling by dividing the intervention and control groups. The study used a pretest-posttest control group design method by comparing the use of the MEOWS and the Poedji Rochjati Scorecard (KSPR) to the number of public health center referrals in Semarang. The data obtained will be analyzed statistically with the bivariate test, Mann-Whitney difference test, relative risk reduction, and absolute risk reduction.Results: The results showed that 21 of 43 (48.8%) patients were referred to the control group and 26 of 36 (72.2%) patients were referred to the intervention group. Mann-Whitney test of the number of referrals after the intervention within 3 months showed significant results (p = 0.033; p <0.05). There was an increase in the number of maternal referrals at the public health center in Semarang after the implementation of the MEOWS score by 1.48 times compared to using the KSPR (RR : 1.48 ; 95% CI : 1.02 – 2.13).Conclusion:The use of the MEOWS score can increase awareness of potential referrals and is associated with complications in patients.Background: The maternal mortality rate in Semarang is 121.5 per 100,000 live births, the second-highest in Central Java. The early warning system with the Early Warning Score and the maternal emergency early warning system (PDKM) still has various shortcomings to reduce MMR.Objective: This study aims to prove the effectiveness of the application of the PDKM Modified Early Obstetric Warning System (MEOWS) as an assessment of the risk of pregnancy in primary health facilities to reduce MMR in Semarang.Methods: The study was conducted on all pregnant women who came to Tlogosari Wetan, Tlogosari Kulon, Bandarharjo, and Bangetayu public health center in Semarang and were willing to participate in the study and were referred to government hospitals using national health assurance BPJS. Sampling was done by cluster random sampling by dividing the intervention and control groups. The study used a pretest-posttest control group design method by comparing the use of the MEOWS and the Poedji Rochjati Scorecard (KSPR) to the number of public health center referrals in Semarang. The data obtained will be analyzed statistically with the bivariate test, Mann-Whitney difference test, relative risk reduction, and absolute risk reduction.Results: The results showed that 21 of 43 (48.8%) patients were referred to the control group and 26 of 36 (72.2%) patients were referred to the intervention group. Mann-Whitney test of the number of referrals after the intervention within 3 months showed significant results (p = 0.033; p <0.05). There was an increase in the number of maternal referrals at the public health center in Semarang after the implementation of the MEOWS score by 1.48 times compared to using the KSPR (RR : 1.48 ; 95% CI : 1.02 – 2.13).Conclusion: The use of the MEOWS score can increase awareness of potential referrals and is associated with complications in patients.